Spinal anaesthesia for day case surgery. - Clarke, G. A. (Royal College of Surgeons of England, 1988)
Postoperative morbidity in fifty day care patients undergoing spinal anaesthesia was evaluated by means of a postoperative questionnaire. Despite the use of a 26G spinal needle in all patients, there was an overall incidence of spinal headache of 18%, which rose to 39% when considering patients under 40 years of age. Several spinal headaches of three to five days' duration were reported. Patients receiving spinal anaesthesia were compared with a smaller group of patients receiving general anaesthesia for similar procedures, and this group showed no evidence of post-operative morbidity after 48 h. In agreement with a previous study, it is concluded that spinal anaesthesia is not a suitable technique for the young day care patient.